Requirements for the accuracy of the existing and newly built planned geodesic networks in the area (Texas Journal of Agriculture and Biological Sciences, 2023)
This article covers in detail the requirements for them when building state geodesic nets. Concepts are also given about the accuracy and mechanism of operation of the height networks of State geodesic networks.